Alternative public space: experiences and lessons from Indonesian cities. Issue 2 (20th May 2022) - Panjaitan, Tigor Wilfritz Soaduon; Pojani, Dorina; Darchen, Sébastien
Abstract : This study centres on alternative public space in Indonesian cities in the post-Reformation era. Through in-depth interviews with experts and personal observations of a variety of public spaces in Bandung and Surabaya, the authors explore: ( a ) the concept of 'alternative public space' in the context of Indonesian cities, ( b ) the actors that have driven the emergence of these 'alternative public spaces' and their motivations and ( c ) issues around the management and maintenance of 'alternative public space'. It was found that the role of the community is very significant here. Alternative public spaces are not necessarily publicly owned, managed and maintained. However, these shortcomings do not necessarily result in negative outcomes, as long as alternative public spaces are not co-opted but continue to fulfil community needs and aspirations.